Evaluation of the in vivo wound healing potential of the lipid fraction from activated platelet-rich plasma. (18th May 2020) - Cakin, Mehmet Can; Ozdemir, Busra; Kaya-Dagistanli, Fatma; Arkan, Hulya; Bahtiyar, Nurten; Anapali, Merve; Akbas, Fahri; Onaran, Ilhan
Abstract: Previous in vitro studies suggest a direct relevance for the peptide–free lipid fraction (LF) of platelet-rich plasma (PRP) in biological mechanisms related to wound healing. However, there are no scientific reports to date on the wound healing activities of this lipid component in vivo . Thus, the present study provides a scientific evaluation for the wound healing potential of the lipid portion of the activated PRP. For the wound healing activity assessment, in vivo full‐thickness excisional wounds were created on the dorsal skin of Sprague-Dawley rats. Lipid extract from pooled PRP was applied topically to the wounds on 0, 3, and 7 days after injury. Histological assessment of epidermal and dermal regeneration, granulation tissue thickness and angiogenesis by Sirius red and Masson's trichrome staining, in addition to immunohistochemical staining for transforming growth factor beta-1 (TGF-β1), collagen type I (COL I), and collagen type III (COL III) were performed on skin biopsies at 3, 7 and 14 days. The total histological scores of the LF group were significantly higher than the 25% dimethylsulfoxide-control group. According to the immunohistochemical staining, the observed expression changes for TGF-β1, COL I and III at 3, 7, and 14 days after wounding were significantly better in the study group than the control group. Furthermore, COL I/III ratio in the lipid extract-treated group at day 14 was much higher than that of the control group. Meanwhile, analysis of the data also indicated that the LF has less positive effects on all evaluated parameters than PRP. From the present data, it could be concluded that the peptide–free LF of PRP has potent wound healing capacity in vivo for cutaneous wounds, although not as much as that of PRP. Strengthening our understanding of the wound healing potential of lipid components of PRP and platelet-derived lipid factors may provide new avenues for improving the healing process of a wound with elevated protease activity. Graphical abstract: